Physicochemical, Antioxidant And Antibacterial Properties Of Betel Leaf And Kaffir Lime Essential Oil Nanoemulsions - Khor, Ru Mei (Universiti Sains Malaysia, 2021)
The current study focused on the characterization of physicochemical, antioxidant and antibacterial properties of betel leaf (Piper betle L.) and kaffir lime (Citrus hystrix) essential oil (EO) nanoemulsion prepared using spontaneous emulsification method. Three stable EO nanoemulsions, namely betel leaf EO nanoemulsions, kaffir lime EO nanoemulsions and betel:kaffir EO nanoemulsions were prepared.